The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1097/00006676-200108000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Germ Extract Decreases Glucose Uptake and RNA Ribose Formation but Increases Fatty Acid Synthesis in MIA Pancreatic Adenocarcinoma Cells

Abstract: The fermented wheat germ extract with standardized benzoquinone composition has potent tumor propagation inhibitory properties. The authors show that this extract induces profound metabolic changes in cultured MIA pancreatic adenocarcinoma cells when the [1,2-13C2]glucose isotope is used as the single tracer with biologic gas chromatography-mass spectrometry. MIA cells treated with 0.1, 1, and 10 mg/mL wheat germ extract showed a dose-dependent decrease in cell glucose consumption. uptake of isotope into ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…Similar to the relevance of Her2/neu as a 'drugable' target for an individualized anti-cancer therapy (22)(23)(24)(25), TKTL1 might also be a future target for small molecule drug design and individualized treatment strategies in breast cancer: metabolic control analysis and inhibition of transketolase enzyme reactions have shown in vitro as well as in vivo that tumor proliferation can be inhibited by antitransketolase approaches (5)(6)(7)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the relevance of Her2/neu as a 'drugable' target for an individualized anti-cancer therapy (22)(23)(24)(25), TKTL1 might also be a future target for small molecule drug design and individualized treatment strategies in breast cancer: metabolic control analysis and inhibition of transketolase enzyme reactions have shown in vitro as well as in vivo that tumor proliferation can be inhibited by antitransketolase approaches (5)(6)(7)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that Avemar controls tumor propagation primarily through the regulation of glucose carbon redistribution between cell proliferation-and cell differentiation-related macromolecules in MIA cells (3). In the present study we again applied stable isotope-based dynamic metabolic profiling as a model for measuring metabolic pathway control characteristics (29) by demonstrating a dose-dependent decrease in substrate carbon flow toward nucleic acid precursor ribose synthesis and metabolic enzyme activities (G6PDH, transketolase, HK, and LDH) in Jurkat leukemia cells treated with comparable doses of Avemar.…”
Section: Discussionmentioning
confidence: 99%
“…Although no chemical constituents are yet isolated and tested experimentally, it is likely that benzoquinones and wheat germ agglutinin in wheat germ and fiber and lipids and phytic acid in wheat bran play a significant role in exerting anti-carcinogenic effects. In a recent report utilizing intracellular carbon flow studies with a 13 C-labeled isotope of glucose and biological mass spectrometry (GC/MS), 1 it was demonstrated that the crude powder of fermented wheat germ dosedependently inhibits nucleic acid ribose synthesis primarily through the nonoxidative steps of the pentose cycle while increasing direct glucose carbon oxidation and acetyl-CoA utilization toward fatty acid synthesis in pancreatic adenocarcinoma cells (3). These metabolic changes indicate that fermented wheat germ exerts its anti-proliferative action through altering metabolic enzyme activities, which primarily control glucose carbon flow toward nucleic acid synthesis.…”
mentioning
confidence: 99%
“…18 In addition, dietary studies indicate that the inhibition of the PPP suppresses tumor growth. [19][20][21][22][23][24][25][26][27] Therapeutic selectivity by preferential killing cancer cells without significant toxicity to normal cells is one of the most important considerations in cancer therapy. Understanding the biological differences between normal and cancer cells is essential for the design and development of such selective anticancer drugs.…”
mentioning
confidence: 99%